Amelioration of hyperglycaemia and modulation of pro-inflammatory cytokines by Tamarix gallica fractions in alloxan induced diabetic rats. (2nd November 2022) - Malik, Maryam; Sharif, Ali; Hassan, Saeed Ul; Muhammad, Faqir; Khan, Humaira Majeed; Akhtar, Bushra; Saeed, Myeda
Abstract: Present study is engrossed in identification of phyto-constituents from aerial part extracts of Tamarix gallica and appraisal of its anti-oxidant, anti-diabetic and anti-inflammatory potential based upon its folktale use. The methanol and n -hexane fractions of aerial parts were analysed using high performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS) respectively. Inhibitory concentration (IC50 ) showed better results in case of methanolic extract for both in antioxidant (IC50 = 15.47 µg/mL) and alpha amylase (IC50 =18.75 µg/mL) assays. Significantly higher quantities of phenolic and flavonoid contents were present in methanolic extract. A significant correlation was found to be existed between these contents and IC50 of antioxidant assay. Alloxan induced hyperglycaemia declined along with improvement in lipid profile, C-reactive proteins (CRP), liver function tests (LFTs) and renal function tests (RFTs). Methanolic fraction (500 mg/kg) was also related to significant reduction in levels of inflammatory markers i.e. tumour necrosis factor-alpha, TNF- α (1.28 ± 0.13 g/L) and interleukin-6, IL-6 (98 ± 10.4 pg/L) as observed in diabetic rats. Based upon the above findings, the study suggests that methanolic fraction from aerial parts of the T. gallica has better anti-diabetic profile which might be attributed to its alpha amylase, anti-oxidant and anti-inflammatory potential.